Integrated strategy approach for poverty alleviation in developing countries - DERBAL, Abdelkader (Journal of Human Sciences, 1999)
Pr DERBAL Abdelkader Institut des Sciences Commerciales Université d’Oran, Algérie In this paper we attempt to show that there are different ways of defining and measuring poverty. Then we go on to analyse the theory of poverty before addressing the important issue of income distribution during the development process. Finally the issue of anti-poverty policies is addressed to this end the following policy turgets are set. i. increase the quantity of assets owned by the poor. ii. increase the volume of their market rules. iii. increase the prices of the services they sell.